2018
DOI: 10.1111/1753-6405.12709
|View full text |Cite
|
Sign up to set email alerts
|

Inclusion of equity in economic analyses of public health policies: systematic review and future directions

Abstract: Objectives: To assess current approaches to inclusion of equity in economic analysis of public health interventions and to recommend best approaches and future directions. Methods:We conducted a systematic review of studies that have used socioeconomic position (SEP) in cost-effectiveness analyses. Studies were identified using MedLine, EconLit and HEED and were evaluated based on their SEP specific inputs and methods of quantification of the health and financial inequalities.Results: Twenty-nine relevant stud… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
24
0
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 31 publications
(25 citation statements)
references
References 57 publications
0
24
0
1
Order By: Relevance
“…Also, the participants revealed that minimising inequalities was an important criterion for public health decision making. Methods for incorporating equity into economic evaluation are under development within health economics (Round and Paulden, 2018), however, there are few examples of this being applied to public health interventions (Lal et al , 2018). This study provides further evidence that this is an important research area for supporting local public health decision making.…”
Section: Discussionmentioning
confidence: 99%
“…Also, the participants revealed that minimising inequalities was an important criterion for public health decision making. Methods for incorporating equity into economic evaluation are under development within health economics (Round and Paulden, 2018), however, there are few examples of this being applied to public health interventions (Lal et al , 2018). This study provides further evidence that this is an important research area for supporting local public health decision making.…”
Section: Discussionmentioning
confidence: 99%
“…Creating a systems value across all levels of the health system and government may be an essential starting point to advocate for necessary structural change that addresses root causes of inequities [ 45 ]. Careful consideration of how economic arguments, including costs effectiveness analyses, might be structured to explicitly weigh health equity is a potential strategy for attempting to counter this [ 58 – 60 ]. Development of health equity indicators and surveillance measures, including those related to structural determinants, are needed to demonstrate burden and gradients in health outcomes [ 61 , 62 ].…”
Section: Discussionmentioning
confidence: 99%
“…Since the 1978 Declaration of Alma-Ata, citations in MEDLINE that include the term "equity" increased by 216% in 2015 compared to 1980 [18]. Given the increase in publications, comprehensive reviews and analyses on equity consideration in economic evaluations have also been conducted, though most reviews have focused on specific methodologies of how to integrate equity concerns into economic evaluations [19][20][21]. Other reviews have been based on specific interventions or concepts, such as vaccines, operation research, and universal health coverage [9,18,22].…”
Section: Health Equity As a Part Of Health Economic Evaluationsmentioning
confidence: 99%